STRATEGI PEMECAHAN MASALAH DALAM MATEMATIKA - Karsoni Berta Dinata (Universitas Muhammadiyah Kotabumi, 2017)
The main purpose of studying mathematics is to find ways to solve problems or mathematics problems. What is meant by problems or mathematics problems is a thing that final result, or how to solve it is not known. In solving mathematical problems there are several strategies that can be used that are: direct proof, indirect proof, verification with contradiction, proof with examples of denying, reverse working strategy, pattern discovery, and the use of bird house principles.